2010
DOI: 10.1080/15389580903390623
|View full text |Cite
|
Sign up to set email alerts
|

Do Light Truck Vehicles (LTV) Impose Greater Risk of Pedestrian Injury Than Passenger Cars? A Meta-analysis and Systematic Review

Abstract: Our systematic review and meta-analysis suggests that LTVs pose a greater risk of pedestrian injury death compared to conventional cars. These findings have important implications for the automotive industry and the safety of vulnerable road users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Most belonged to the light truck vehicle (LTV) category, which has been widely studied in relation to injury severity in pedestrian crashes. Desapriya, in a recent meta-analysis (Desapriya et al 2010), found a 1.54-fold higher risk of pedestrian death (95% CI, 1.15;1.93) associated with LTVs than passenger cars, comparable to the present finding of 2.21 (1.32;3.71).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Most belonged to the light truck vehicle (LTV) category, which has been widely studied in relation to injury severity in pedestrian crashes. Desapriya, in a recent meta-analysis (Desapriya et al 2010), found a 1.54-fold higher risk of pedestrian death (95% CI, 1.15;1.93) associated with LTVs than passenger cars, comparable to the present finding of 2.21 (1.32;3.71).…”
Section: Discussionsupporting
confidence: 79%
“…The main location of the first impact on the vehicle was considered, but found not to be significant when impact speed was taken into account. Regarding car dimensions, many studies have shown that LTVs are associated with greater risk of pedestrian injury or fatality than passenger cars (Desapriya et al 2010;Roudsari et al 2005). This result is in concordance with the higher risk associated with vans than passenger cars in the present study (see Table 1).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Despite the differences, it is reasonable to expect that factors that are highly influential for the outcome for struck pedestrians will also influence the outcome for struck bicyclists; e.g., impact speed (Rosén and Sander, 2009;Tefft, 2011), age (Henary et al, 2006;Peng and Bongard, 1999), vehicle type (Desapriya et al, 2010;Lefler and Gabler, 2004) and mean travel speed of motorized vehicles (Kröyer, 2014). This article has two aims: (1) to analyze the relation between the injury severities of struck bicyclists, the age of the victim and the mean travel speed at the accident location.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to factors related to impact, vehicle type has also been shown to influence injury severity. The risk of pedestrian fatality for example, is greater in collisions involving vans or sport utility vehicles (SUVs) compared with passenger vehicles (Desapriya et al, 2010;Lefler and Gabler, 2004). Meanwhile, vehicle safety features such as passenger detection systems including automatic braking strongly influence pedestrian safety.…”
Section: Introductionmentioning
confidence: 99%